Pengembangan E-Modul Asam Basa Model Project Based Learning (PjBL) Terintegrasi Science, Technology, Engineering, Art, And Mathematics (STEAM) pada Peserta Didik SMKN 9 Bulukumba - Nurhayati, Nurhayati; Sulastry, Taty; Aulia, Army (Chemistry Education Review (CER), 2023)
This research is a development research that aims to develop and produce an acid- base E-Module with Project Based Learning (PjBL) integrated Science, Technology, Engineering, Art, and Mathematics (STEAM) which has valid, practical, and effective criteria. The development model used in the study refers to the ADDIE development model, which consists of the analisys stage, the design stage, the development stage, the implementation stage, and the evaluation stage. The acid-base E-Module with PjBL integrated STEAM developed was validated by two experts. After being validated, the acid- base E-Module with PjBL integrated STEAM was  piloted  on students at grade X TKJ 1 at SMKN 9 Bulukumba of academic year 2021/2022 with 27 students. The results show that the acid-base E-Module with PjBL integrated STEAM developed had conducted a validation process, measuring the level of practicality and effectiveness. The E-Module is stated as valid based on the results of the E-Module validation with an average value of 3.42 (vaery valid). The E-Module is stated aspractical based on: (1) the implementation of the acid-base e-module based on problem-based learning at an average value of 1.9 (fully implemented), (2) the teacher's response with an average score of 97.12 (very practical), and (3) the students’ responses with an average score of 81.34 (very practical). E-module is stated as effective based on the results of the N-gain test of 0.76 (high) and classical completeness of 85.19%. Therefore, the results of the study indicate that the acid-base E-Module with PjBL integrated STEAM has valid, practical, and effective qualities. An outline summary of the acid-base E-Module with PjBL integrated STEAM contains a glossary, basic competencies, competency achievement indicators, instructions for using e- modules, concept maps,  learning activities 1, 2, 3, and  4,  evaluation  and answer keys.